REDESAIN KOLAM RENANG MUARA KAPUAS DI KOTA PONTIANAK - Nanda, Agustinus; Muazir, Syaiful; Mustikawati, Mustikawati (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Indonesia has significant natural potential in the tourism sector, one of which is the Kapuas River located in West Kalimantan Province. The Muara Kapuas Swimming Pool, situated along the banks of the Kapuas River, has the potential to be developed to support the growth of the tourism sector. This study discusses the redesign efforts of the Muara Kapuas Swimming Pool in Pontianak into a waterpark-based facility to increase the number of attractions, improve facility quality, and optimize the existing resources. The design method applied is a redesign approach consisting of preparation, data collection, analysis, concept synthesis, final design, and evaluation stages, based on redesign theory, tourism principles, and waterpark standards. The analysis results indicate the need for enhancements to main attractions, optimization of supporting and complementary facilities, as well as development of site massing and design concepts inspired by the Muara Kapuas philosophy and its functional requirements. This redesign is expected to establish the Muara Kapuas Swimming Pool as a waterpark-based tourist destination that can further contribute to the growth of regional tourism.